2018
DOI: 10.1002/ece3.4034
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of pathogen levels is necessary to compare responses to pathogen exposure: Comment on Davy et al. “The other white‐nose syndrome transcriptome”

Abstract: When studying host responses to the presence of pathogens, the pathogen levels should be verified within the samples. The RNA‐Seq samples from Davy et al. (2017) do not contain detectable Pseudogymnoascus destructans pathogen levels compared to other studies. Future studies will be necessary to determine how hosts resistant to white‐nose syndrome respond differently than susceptible hosts at the whole‐transcriptome level. Linked Article: https://doi.org/10.1002/ece3.4035

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…The RNA‐Seq data showed that the 12 UV‐negative biopsies contained 6,650 ± 8,190 P. destructans transcripts. The reads that map to the P. destructans transcriptome represent 0.10% ± 0.12% of the total mapped reads in the UV‐negative samples, similar to what we find in tissue samples from bats with no exposure to P. destructans (Field, ). The 12 UV‐positive biopsies contained significantly more transcripts (190,000 ± 181,000, p = 0.004, paired t test).…”
Section: Methodssupporting
confidence: 79%
“…The RNA‐Seq data showed that the 12 UV‐negative biopsies contained 6,650 ± 8,190 P. destructans transcripts. The reads that map to the P. destructans transcriptome represent 0.10% ± 0.12% of the total mapped reads in the UV‐negative samples, similar to what we find in tissue samples from bats with no exposure to P. destructans (Field, ). The 12 UV‐positive biopsies contained significantly more transcripts (190,000 ± 181,000, p = 0.004, paired t test).…”
Section: Methodssupporting
confidence: 79%
“…There were, therefore, no pathogen loads to quantify in the exposed tissue (Davy et al., ). We thank Field () for confirming that P. destructans was virtually undetectable in the wing tissue of exposed M. myotis, as we also reported in our study.…”
Section: Pseudogymnoascus Destructans Did Not Invade the Tissue Of Exsupporting
confidence: 88%
“…(), “The Other White‐Nose Syndrome Transcriptome: tolerant and susceptible hosts respond differently to the pathogen Pseudogymnoascus destructans”, where we reported the outcomes of experimental exposure of little brown bats, Myotis lucifugus, and greater mouse‐eared bats, Myotis myotis, to P. destructans . Field () raises three key points: (1) that the putatively tolerant species in our experiment ( M. myotis ) did not develop infection, (2) that the reported qPCR results do not confirm the presence of the pathogen at the time of sampling, and (3) that the M. myotis tissue used for RNA sequencing did not contain the pathogen, P. destructans . These points highlight the unique challenges of studying host–pathogen interactions in environmentally persistent pathogens, and we welcome the opportunity to explicitly discuss these challenges.…”
mentioning
confidence: 88%
See 2 more Smart Citations